A Multimodal Study of Selected Campaign Posters of All Progressives Congress's Presidential Candidate in Nigeria 2023 General Elections - Davidson M. Omole; Ugoala, Bibian (Universitas Negeri Yogyakarta, 2025)
This study is a multimodal analysis of selected political campaign posters of Bola Ahmed Tinubu